Cytochrome c Oxidase Sequences of Zambian Wildlife Helps to Identify Species of Origin of Meat. (22nd November 2016) - Syakalima, Michelo; Munyeme, Musso; Yasuda, Jun
Abstract : Accurate species identification is a crucial tool in wildlife conservation. Enforcement of antipoaching law is more achievable with robust molecular identification of poached meat. Determining the region where the animal may have been taken from would also be a useful tool in suppression of cross-border trade of poached meat. We present data from a cytochrome c oxidase "barcoding" study of Zambian ruminants that adequately identifies the species of origin of meat samples. Furthermore, the method demonstrates possible improvement and application in regional variation in sequence identity that has a potential for discriminating meat samples from different subpopulations.